Impact load measurement of small multi-bubble explosions near solid wall - Nyo Me Thet Naing; Seung-Ho Hyun; Rho-Taek Jung (International Journal of Naval Architecture and Ocean Engineering, 2024)
The interaction of multiple spark-generated bubbles near solid boundary is investigated experimentally. Qualitative study is done with high-speed imaging for bubble shape evolution and PVDF sensor for impact force measurement. Similar-sized bubbles are created synchronously and distance between bubbles or boundary is chosen to be as small as possible. The jet direction of two horizontally aligned bubbles is strongly influenced by proximity parameter (γ) near boundary. The role of inter bubble distance (η) between bubbles and its contribution to intensity of impulsive force is also presented. It is found that strongest impact is recorded for horizontal pair, compared to vertical pair and diagonal pair, for small η values. Three bubbles are arranged with middle one which is smaller, similar or bigger than left and right bubbles. Allocating bigger bubble in the center indeed produces the most destructive impact on boundary among all cases. Moreover, diverse bubble deformation features are witnessed for various combination of dimensionless parameter applied in this study.